Evaluating the Efficiency of Polyhedral Mesh Elements in Solving the Problem of the Flow around Ship’s Rudder - Ibraheem, Amjd (International Journal of Engineering and Management Sciences, 2021)
Meshing is one of the crucial key features to the success of CFD based simulations, this study is evaluating the efficiency of polyhedral elements in solving the problem of the flow around ship rudder, using a Reynolds-averaged Navier-Stokes turbulence model (SST k-ω), and compares it to a tetrahedral based mesh, considering that polyhedral elements were neglected in the past due to difficulties in implementing them, this was solved by introducing a tool by ANSYS that converges tetrahedral elements to polyhedral element, and integrating it into FLUENT software, the model was validated by comparing it with previously validated model which used the full version of ANSYS, this study was concluded using the academic version, but still it was able to produce satisfying results in predicting the lift and the drag coefficient, the pressure around the rudder surface, the velocity and the turbulent kinetic energy, finally the mesh quality was evaluated using the orthogonal quality criteria, the results showed the supremacy of the polyhedral elements in saving time and computational resources and improving mesh quality, and keeping high level of accuracy in predicting the results.